L-arginine combination with 5-fluorouracil inhibit hepatocellular carcinoma cells through suppressing iNOS/NO/AKT-mediated glycolysis - Hu, Yile; Xing, Yihao; Fan, Gaolu; Xie, Huaxia; Zhao, Qingzan; Liu, Ling (Frontiers in Pharmacology, 2024)
L-arginine can produce nitric oxide (NO) under the action of inducible nitric oxide synthase (iNOS), while 5-fluorouracil (5-FU) can induce the increase of iNOS expression. The present study was to investigate the mechanism of L-arginine combined with 5-FU regulating glucose metabolism of hepatocellular carcinoma (HCC) through iNOS/NO/AKT pathway. The combination of L-arginine and 5-FU resulted in decreased cell survival and exhibited synergistic cytotoxic effects in HepG2 and SMMC7721 cells. Meanwhile, L-arginine increased 5-FU inhibitory effect on HepG2 and SMMC7721 cells by increasing NO production. Cotreatment with L-arginine and 5-FU resulted in a significant decrease in both G6PDH and LDH enzymatic activities, as well as reduced levels of ATP and LD compared to treatment with L-arginine or 5-FU alone. Moreover, the combination of L-arginine and 5-FU resulted in a decrease in the expression of GLUT1, PKM2, LDHA, p-PI3K and p-AKT. Furthermore, the combination demonstrated a synergistic effect in downregulating the expression of HIF-1α and β-catenin, which were further diminished upon the addition of shikonin, a specific inhibitor of PKM2. LY294002 treatment further reduced the expression of GLUT1, PKM2, and LDHA proteins induced by combined L-arginine and 5-FU treatment compared to the combined group. However, the reduction in p-PI3K, p-AKT, and GLUT1 expression caused by L-arginine and 5-FU combination was also reversed in HepG2 and SMMC7721 cells with iNOS knockdown, respectively. Additionally, the combination of Larginine and 5-FU led to a greater reduction in the enzymatic activity of ALT, AST, G6PDH and LDH, as well as a significant reduction in hepatic index, AFP, AFP-L3, ATP and LD levels in a rat model of HCC. Moreover, the simultaneous administration of L-arginine and 5-FU significantly improved the gross morphology of the liver, reduced nuclear atypia, inhibited the proliferation of cancer cells, and decreased the expression levels of p-PI3K, p-AKT, GLUT1, PKM2, and LDHA, while iNOS expression was increased in the combination group. Taking together, L-arginine and 5-FU combination resulted in the inhibition of enzymes in aerobic glycolysis via the iNOS/NO/AKT pathway, which led to the suppression of glucose metabolism and downregulation of nuclear transcription factors, thereby impeding the proliferation of hepatocellular carcinoma cells.